ISSUES OF IMPLEMENTING IFRS 1 (“Presentation of Financial Reporting”) STANDARD IN COMMERCIAL BANKS ON THE EXAMPLE OF “ASAKABANK” JSC” - Ruziyev Elyor Zafar oglu (Scholar Express Journals, 2025)
In recent years, one of the important areas of reforms implemented in the process of modernization of the banking and financial system of Uzbekistan is the issue of adapting the accounting and financial reporting system to international standards. International Financial Reporting Standards (IFRS) help increase investment attractiveness, provide transparent and comparable information for investors, creditors and the general public. In this regard, IFRS 1 - the standard “Presentation of Financial Reporting” is of particular importance in the activities of commercial banks
Keywords: Asakabank” JSC”